The role of p53 mutations as a prognostic factor and therapeutic target in inflammatory breast cancer. (April 2006) - Yang, Charles H; Cristofanilli, Massimo
Inflammatory breast cancer is a rare but lethal form of locally advanced breast cancer. Despite improvements in survival with the advent of multidisciplinary treatment regimens, 5-year survival rates remain disappointing, at approximately 30%. Numerous molecular markers have been investigated for their potential as useful prognostic and predictive markers of treatment response that would impact on the management of inflammatory breast cancer. This review discusses the current status of p53 mutations both as a prognostic marker and as a potential target for directed therapies.